2015
DOI: 10.4254/wjh.v7.i7.1001
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume as a novel predictor of systemic inflammatory response in cirrhotic patients with culture-negative neutrocytic ascites

Abstract: Our results support that MPV can be an useful predictor of systemic inflammatory response syndrome in cirrhotic patients with AFI, particularly CNNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The studies also suggest that the MPV increases more in cirrhotic patients with infections especially SBP and that it is affected by the severity of the systemic inflammatory response syndrome (SIRS) associated with these infections. MPV can be the earliest laboratory tests that can provide a rapid diagnostic tool for AFI even before you perform ascetic fluid sampling and examination [8].…”
Section: Introductionmentioning
confidence: 99%
“…The studies also suggest that the MPV increases more in cirrhotic patients with infections especially SBP and that it is affected by the severity of the systemic inflammatory response syndrome (SIRS) associated with these infections. MPV can be the earliest laboratory tests that can provide a rapid diagnostic tool for AFI even before you perform ascetic fluid sampling and examination [8].…”
Section: Introductionmentioning
confidence: 99%
“…MPV levels have been found higher in cirrhotic patients with AFI than in those without bacterial infection or in healthy controls [16,28]. And also, MPV has been described as a diagnostic predictor for AFI and a novel and useful predictor of systemic inflammatory response syndrome in cirrhotic patients with AFI [16,28].…”
Section: Mpv and Brucellosismentioning
confidence: 99%
“…MPV levels have been found higher in cirrhotic patients with AFI than in those without bacterial infection or in healthy controls [16,28]. And also, MPV has been described as a diagnostic predictor for AFI and a novel and useful predictor of systemic inflammatory response syndrome in cirrhotic patients with AFI [16,28]. Whereas no significant relation between MPV and Dengue fever has been demonstrated, increased MPV values in malaria have been defined as a useful predictive marker for severity of infection [12,29].…”
Section: Mpv and Brucellosismentioning
confidence: 99%
“…While no Child-A case was identified, there were more Child C cases than Child-B cases. According to the study fulfilled by Galvez-Martinez et al [11] they detected no clear difference in ages between the SAI+ and SAI-groups, but they showed significant elevation for the female sex among all cases. Additionally, as in our study, the highest rate was found for culture negative neutrocytic ascites.…”
Section: Discussionmentioning
confidence: 87%